How care work employment shapes earnings in a cross-national perspective - Michelle J. Budig; Joya Misra (Luxembourg Income Study (LIS), 2008)
This report investigates the effect of employment in a job involving care work - conceptualized as work in occupations where workers provide face-to-face services that strengthen the physical health and safety or the physical, cognitive, or emotional skills of those they serve - on the relative earnings of both men and women workers in twelve countries that represent a range of economic and political policy contexts. In addition, this report descriptively explores the characteristics of workers engaged in care employment and how these vary cross-nationally. We examine how much of the effects of care work employment on wages can be attributed to differences in worker characteristics such as educational attainment, age, gender, and nativity. Importantly, where possible, we disaggregate our category of care workers into smaller occupational groups, namely physicians, nurses, primary/secondary teachers, university professors, and domestic workers versus all other care workers to examine whether the effect of care work employment on earnings varies by the type of care work performed. We also discuss three major explanations for the potential differential pay of care workers: cultural devaluations of care work due to its association with 'women's work,' economic tensions due to the expense of high quality care provision, and political factors shaping labor market and social inequalities regarding care work. We consider how national context and social policies - including the degree of country-level earnings inequality, size of public sector, immigration, and labor union density - shape variation in the relative net effects of care work on earnings.
Keywords: 330; Pflegeberufe; Lehrkräfte; Geschlecht; Lohnstruktur; Lohnstruktur; Vergleich